2012
DOI: 10.1109/tgrs.2011.2170177
|View full text |Cite
|
Sign up to set email alerts
|

Validation of SMOS Brightness Temperatures During the HOBE Airborne Campaign, Western Denmark

Abstract: The Soil Moisture and Ocean Salinity Mission (SMOS) delivers global surface soil moisture fields at high temporal resolution which is of high relevance for water management and climate predictions. For data validation, an airborne campaign with the L-band radiometer EMIRAD-2 and concurrent ground sampling was carried out within one SMOS pixel in the Skjern River Catchment, Denmark. By means of this dataset the objective of this study is a step-wise comparison of brightness temperatures from point via air-to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 65 publications
6
58
0
Order By: Relevance
“…Examples are Albergel et al (2011), Montzka et al (2011), Parrens et al (2012 and Bircher et al (2012). Albergel et al (2011) and Parrens et al (2012) have shown that there is still potential to improve soil moisture retrievals from SMOS brightness temperatures in southern France.…”
Section: F Schlenz Et Al: Analysis Of Smos Brightness Temperature Amentioning
confidence: 99%
See 2 more Smart Citations
“…Examples are Albergel et al (2011), Montzka et al (2011), Parrens et al (2012 and Bircher et al (2012). Albergel et al (2011) and Parrens et al (2012) have shown that there is still potential to improve soil moisture retrievals from SMOS brightness temperatures in southern France.…”
Section: F Schlenz Et Al: Analysis Of Smos Brightness Temperature Amentioning
confidence: 99%
“…They used calibrated statistical relationships based on reference soil moisture values and additional information like leaf area index (LAI) simulated by a land surface model to produce better soil moisture estimates. Bircher et al (2012) have compared SMOS L1c and airborne brightness temperatures with modelled brightness temperatures using in situ data as input on different spatial scales on one day in Denmark. They developed an improved L-MEB parameterisation for local conditions.…”
Section: F Schlenz Et Al: Analysis Of Smos Brightness Temperature Amentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their coarse resolution and the complex retrieval algorithms for the signals in steep topographic terrains, they are unable to capture the true soil moisture in regions with pronounced topography that changes over small spatial scale. Furthermore, the in situ soil moisture measurements necessary for the validation of remote sensing products (e.g., Albergel et al, 2011;Bircher et al, 2012;Rautiainen et al, 2012;Magagi et al, 2013) are also sparse in these areas, since measurements in mountainous terrains are costly to implement and were so far not in the focus of climatic studies. Although, the influence of soil moisture on the thermal regime of frozen ground was confirmed in many modeling studies (e.g., Hinkel et al, 2001;Boike et al, 2008;Westermann et al, 2009;Scherler et al, 2010) soil moisture measurements remain restricted to uncoordinated and project based installations (e.g., Hilbich et al, 2011;Rist and Phillips, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As reference, in situ time domain reflectometry (TDR) or frequency domain (FD) probes and gravimetric measurements are used as well as model approaches [28][29][30][31][32][33][34]. A comprehensive overview on in situ SM measurements from many different networks around the globe can be obtained in the International Soil Moisture Network (ISMN) [35].…”
Section: Introductionmentioning
confidence: 99%